TAHLīLU MUHTAWĀ TAʿLīMI AL LUĠAT̈I AL ʿARABīATI MIN H̱ILĀLI AL MAWQIʿ AL ILIKTRUNī "BAYYINAH DREAM" WA MUSĀHAMTIHI FI TAʿLīMI AL LUĠAT̈I AL ʿARABīATI Fī ʿAṢRI AL MUJTAMAʿI 5.0 - Abicandra, Muhammad Nidom Hamami; Al Farouqi, Casilda (Critical Review of English-Arabic World Journal, 2024)
Modern education in the era of Society 5.0 provides broad access for all segments of society to educational content. However, providing a learning experience for the Arabic language within the concept of lifelong learning, to understand and delve into the teachings of the Quran as a guide for life, a source of knowledge, and a reference on the teachings of Islam, has not been fully realized and felt by all segments of society. The researcher found that the content of Arabic language education on the website "Bayyinah Dream" serves as an alternative source that can meet the community's needs for learning Arabic for specific purposes, utilizing the concept of lifelong learning and maximizing the use of technology in the learning process. As for the method of collecting his data using observation and documentation. This study aims to explore the Arabic language education content on the "Bayyinah Dream" website as an alternative source to meet community needs. The study describes the program structure, materials, teaching methods, and evaluates its contribution to Arabic language education in Society 5.0. The findings highlight the engaging nature of the program, its alignment with the Quran as a life guide, and the structured arrangement of materials. The content on "Bayyinah Dream" facilitates enjoyable and lifelong learning experiences.